VECM Analysis to House Price Index. Case of Tirana (European Journal of Marketing and Economics, 2020)
This paper analyzes long-run equilibrium of “house price index” in Tirana (the capital city of Albania) achieved by the long-run performance of macroeconomic factors.We have used the techniques and analysis of linear multiple regression by VECM (vector error correction model), to identify endogenous factors, that effect the stability of “house price index”. The analyze is based on data series 2010-2018 (with 3-month frequency), with independent variables: mortgage loan, interest rate on long-term loans, construction cost index, EUR/ALL exchange rate, house price index with lag(1).We conclude that all these independent variable (expect EUR/ALL exchange rate) are statistically significant, in long-run equilibrium and in the elasticity assessment of “house price index”.
Keywords: Real Estate, VECM model, house price index.